2017
DOI: 10.1080/00016489.2017.1290826
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features and prognosis of mumps-associated hearing loss: a retrospective, multi-institutional investigation in Japan

Abstract: Conclusions:The majority of hearing loss due to mumps presents as unilateral profound sensorineural hearing loss, which is refractory to treatment. In rare cases of bilateral total deafness, cochlear implants were beneficial for speech perception. Vaccination against mumps is recommended to prevent mumps-associated hearing loss. Objective: The objective of this study is to investigate the clinical characteristics of hearing loss due to mumps and to evaluate hearing outcomes. Subjects and methods: The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Mumps deafness in most cases is a serious irreversible complication. 15 Recently published Japanese data showed that the incidence of auditory disorders among mumps patients was 0.1–1%. 14 In our study, mumps deafness was noted in 88 of 68,137 patients with mumps, with an incidence of 0.13% (1/774), which was consistent with the above published data.…”
Section: Discussionmentioning
confidence: 99%
“…Mumps deafness in most cases is a serious irreversible complication. 15 Recently published Japanese data showed that the incidence of auditory disorders among mumps patients was 0.1–1%. 14 In our study, mumps deafness was noted in 88 of 68,137 patients with mumps, with an incidence of 0.13% (1/774), which was consistent with the above published data.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that a certain number of patients with sensorineural hearing loss due to asymptomatic mumps exist. Sensorineural hearing loss due to mumps is typically profound, and hearing prognosis is quite poor [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Such SSNHL was judged to be caused by asymptomatic mumps infection, which did not show any symptoms of parotitis. Additionally, 22.4% of patients were reportedly diagnosed with hearing loss due to asymptomatic mumps infection based on the anti-mumps IgM antibody level in the sela [7] according to criteria for diagnosis of mumps deafness established by Acute Severe Hearing Loss Study Group of the Japanese Ministry of Health, Labor and Welfare in 2013 (Table 1) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sensorineural hearing loss is a well-known complication, previously estimated to occur in 1/15,000 to 1/20,000 cases; however, more recent studies have suggested that the frequency could be 1/1000 [ 3 , 7 ]. In the majority of cases, mumps-related hearing loss is profound and resistant to therapeutics [ 8 ]. Live attenuated mumps vaccines, for example, the measles–mumps–rubella (MMR) vaccines, can prevent MuV infections in childhood and serious complications in young individuals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%